2019
DOI: 10.15446/caldasia.v41n2.66576
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad de comunidades de palmas en el Chocó biogeográfico y su relación con la precipitación

Abstract: Los bosques tropicales del Chocó biogeográfico presentan una de las mayores concentraciones de especies de plantas del mundo. Las palmas (Arecaceae) son una de las familias más importantes en las tierras bajas del Chocó, pero su ecología está poco estudiada. Investigamos la diversidad de comunidades de palmas en el Chocó y su relación con la precipitación en 48 transectos distribuidos en un gradiente de 2000–10 000 mm de precipitación. En cada transecto (5×500 m) se identificaron todas las especies de palmas y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
0
0
Order By: Relevance
“…The 0.5° grid cells with the highest diversity in terms of both species and genera are located in the Chocó region (Figure 2b,c). These results, especially for the municipality of Buenaventura, are similar to those presented by Copete et al (2019), where 42 palm species in 2.5 ha in Bahia Malaga were recorded. Copete et al (2019) also demonstrated that palm diversity is correlated with precipitation in the Chocó.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The 0.5° grid cells with the highest diversity in terms of both species and genera are located in the Chocó region (Figure 2b,c). These results, especially for the municipality of Buenaventura, are similar to those presented by Copete et al (2019), where 42 palm species in 2.5 ha in Bahia Malaga were recorded. Copete et al (2019) also demonstrated that palm diversity is correlated with precipitation in the Chocó.…”
Section: Discussionsupporting
confidence: 91%
“…These results, especially for the municipality of Buenaventura, are similar to those presented by Copete et al (2019), where 42 palm species in 2.5 ha in Bahia Malaga were recorded. Copete et al (2019) also demonstrated that palm diversity is correlated with precipitation in the Chocó. Indeed, precipitation is an important factor explaining palm richness in the Chocó (Copete et al, 2019; Gentry, 1986), the rainiest region in the Americas (~11,000 mm per year).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Detailed floristic studies led by Gentry (1986) in 0.1 ha plots in areas with different levels of rainfall in the Chocó revealed differences in species diversity correlated with precipitation. A strikingly similar correlation between species richness, individual abundancy and precipitation was found more recently to occur in palms (Copete et al, 2019). More species have been recorded from plots located in wetter areas of the Chocó than in plots situated in drier localities, even though all sites present higher individual densities compared with most other continental ecosystems around the world (Gentry, 1986).…”
Section: Biogeography Climate and Diversity Of The Chocósupporting
confidence: 80%
“…The department of Chocó hosts almost 3% of plant diversity, including endemic species, tropical forests, and exotic crops [6]. Furthermore, tropical forests have been shown to be essential ecosystems for carbon balance and climate change mitigation [7]. Indeed, Colombia's bioeconomy strategy for 2020-2030 prioritizes the biogeographic Chocó as one of the main regions for developing high-value-added products and services from the plant species that are characteristic of the region [8].…”
Section: Introductionmentioning
confidence: 99%